REVIEW OF THE STRENGTH OF FOX GLUE IN DEVELOPMENT BOOK VOLS TECHNOLOGY USING THE YOSHINO 602 ENGINE - Muhammad Sultan Nasution; Nurjalih -; Abdul Majid (Kreator, 2019)
Competition in the manufacture of raw materials for printing and binding purposes is undeniable, as is the hot glue required for binding on books. The method used in this writing is descriptive method, namely by presenting factual information obtained from observations obtained and seen in the Industrial Practices place. The binding technique without thread or perfect binding is used for binding books, magazines and others. The main ingredient in the perfect binding binding process is glue. Glue greatly affects the production result, if the adjustments are not done properly the temperature of the glue and the thickness of the glue. The purpose of writing this paper is to determine the adhesion strength of Fox brand glue and to find out the problems that occur in the gluing unit during the volume of the book "Technology Development in the Yoshino 602 machine. Fox glue has high adhesion strength and the adhesion dries quickly so as not to waste a lot of time. , Fox glue is also very suitable for binding paper types (coated and uncoated) with a temperature of 1650C-1800C and a side glue temperature of 1400C on the Yoshino 602 machine. So Fox brand glue is very suitable for the binding process of "Technology Development" books using a machine. Yoshino 602 at PT. Putra Nugraha Sentosa. The problems that occur in the gluing unit are the temperature of the glue, the thickness of the glue on the roller and the glue roller, due to the lack of accuracy of the machine operator.Keywords: Adhesion, Glue and Machine